DISTRIBUSI SPASIAL IKAN BERONANG (Siganus canaliculatus) DI PADANG LAMUN SELAT LONTHOIR, KEPULAUAN BANDA, MALUKU [Spatial distribution of rabbitfish Siganus canaliculatus in the seagrass beds of Lonthoir Strait, Banda Archipelago, Moluccas] - Munira Munira; Sulistiono Sulistiono; Zairion Zairion (Jurnal Iktiologi Indonesia, 2010)
This study was carried out from July to December 2009 in three locations of seagrass area at Lonthoir Strait, Banda Archipelago, Moluccas. The aim of study is to analyze seagrass condition and spatial distribution of the rabbitfish Siganus canaliculatus. The result shows that the species density of the seagrass at three stations ranged from 7.48 to 235.50 ind. m-2 with the highest species density is Cymodocea rotundata at station 1 and 2, and Thalassia hemprichii at station 3. The highest abundance of the fish was found at station 1 and the lowest one was at station 2. According the Kruskal-Wallis test, abundance of male and female rabbitfishes were not statistically different at among stations (H = 0.17, P = 0.66 and H = 0.83, P = 0.92). The correspondence analysis shows that there were two groups of habitat of the rabbitfishes in research station. The first group is station 1 and the second one is station 2 and 3.